2019
DOI: 10.24180/ijaws.599005
|View full text |Cite
|
Sign up to set email alerts
|

Konya Merinosunun Mandibula’sı Üzerine Morfometrik Bir Çalışma

Abstract: Çalışma Konya merinos koyunu mandibula'sı üzerinde bazı morfometrik değerleri ortaya koymak amacıyla yapılmıştır. Çalışmada Bahri Dağdaş Uluslararası Tarımsal Araştırma Enstitüsü'nden temin edilen 44-71 kg arasında değişen ağırlıkta 8 adet Konya merinos koyunu mandibula'sı kullanıldı. Konya merinos koyununun mandibula'sı 16 farklı noktalar arası uzunlukları ölçülmüş ve elde edilen değerler diğer koyun ırklarıyla karşılaştırılmıştır. Araştırmada mandibula'nın morfometrik incelemeleri digital kumpas yardımıyla ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In this study, the GOV‐CR parameter was determined as 90.82 ± 0.95 mm in females and 93.50 ± 0.64 mm in males. Among the studies, this parameter was reported as 95.7 ± 27.1 mm in Mehraban sheep (Karimi et al, 2012), 94.20 ± 7.65 mm in Hemshin sheep (Dalga et al, 2017), 108.68 ± 2.36 mm in Hasmer sheep (Özüdoğru, İlgün, & Özdemir, 2019), 110.97 ± 2.95 mm in Konya merino (Özüdoğru et al, 2019b), and 109.86 ± 5.56 mm in Kosovo Bardhoka breed (Özkan et al, 2020). Yilmaz and Demircioglu (2019) stated in their study on gazelle mandible that there was a statistical significance between sexes in the GOV‐CR data; similar to Özkan et al (2020)'s study in the Kosova Bardhoka breed, it was determined in the present study that the GOV‐CR value did not have a statistical significant difference between sexes ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the GOV‐CR parameter was determined as 90.82 ± 0.95 mm in females and 93.50 ± 0.64 mm in males. Among the studies, this parameter was reported as 95.7 ± 27.1 mm in Mehraban sheep (Karimi et al, 2012), 94.20 ± 7.65 mm in Hemshin sheep (Dalga et al, 2017), 108.68 ± 2.36 mm in Hasmer sheep (Özüdoğru, İlgün, & Özdemir, 2019), 110.97 ± 2.95 mm in Konya merino (Özüdoğru et al, 2019b), and 109.86 ± 5.56 mm in Kosovo Bardhoka breed (Özkan et al, 2020). Yilmaz and Demircioglu (2019) stated in their study on gazelle mandible that there was a statistical significance between sexes in the GOV‐CR data; similar to Özkan et al (2020)'s study in the Kosova Bardhoka breed, it was determined in the present study that the GOV‐CR value did not have a statistical significant difference between sexes ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, numerous studies have been carried out in the field of veterinary anatomy in order to reveal the differences between the sexes and within the species based on the measurements taken from the mandible (Dalga et al, 2017; Demiraslan et al, 2014; Özkan et al, 2020; Özüdoğru et al, 2019a, 2019b; Yilmaz & Demircioglu, 2019). Mandible reconstruction is used for treatment and surgery in many fields of medicine (Güzel et al, 2023; Yeter, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on many different species and races using traditional morphometric methods are widely available in the literature Dalga et al 2022;Özcan et al 2010;Karimi et al 2011;Mohamed et al 2016;Dalga et al 2017;Dalga et al2018;Dalga and Aslan 2020;Wehausen and Ramey 2000;Dalga 2020;Jashari et al 2022;Gundemir et al 2020;Yılmaz and Demircioğlu 2020;Özüdoğru et al 2019). In addition to examining evolutionary processes, there are many studies that analyze two-and threedimensional images using the geometric morphometry method (Klingenberg and Marugan 2013;Szara et al 2022;Koçak et al 2023;Pares 2015;Fernandez et al 2023).…”
Section: Introductionmentioning
confidence: 99%